Traditional herbal medicine legislative and regulatory framework: a cross-sectional quantitative study and archival review perspectives - Dubale, Sileshi; Usure, Rashed Edris; Mekasha, Yesuneh Tefera; Hasen, Gemmechu; Hafiz, Firdos; Kebebe, Dereje; Suleman, Sultan (Frontiers in Pharmacology, 2025)
BackgroundThe World Health Organization (WHO) reports that a significant portion of the global population relies on traditional herbal medicine (THM) due to limited access to safe and high-quality modern medical care. In developing countries, it is difficult to guarantee the safety and quality of THM due to weak enforcement of the legal and regulatory framework. Hence, the study attempted to evaluate the country’s legislative and regulatory framework by comparing it with developed and developing countries that have well-established systems and identify gaps for future roadmaps in the THM landscape.MethodsA cross-sectional study and archival review were performed from November 2021 to March 2022 G.C. to contrast the legislative and regulatory framework for THM regulation with other selected countries like Africa, India, and China. A total of 237 regulatory personnel participated in the study. Data were collected through an archive assessment, self-administrative questionnaires, and literature searches. Secondary data were extracted from the archival review, and the findings were summarized and presented in tabular and text formats. The quantitative data were analyzed using Statistical Package for the Social Sciences (SPSS) software version 26, with outputs presented in text, table, and figure form.ResultsThe archival review of the study found that Ethiopia’s THM legislative and regulatory framework is still in a developmental phase, particularly when compared with countries that have more established systems. A cross-sectional study indicated that approximately 79.7% of participants were aware of THM-related content in the current legislation. However, 82.3% reported they had not received any formal training on THM regulations. For future roadmaps, 73.8% of respondents believed the government showed a commitment to supporting THM regulation, though 51.9% of participants noted limited knowledge and awareness of THM practices and product regulations. In terms of quality, safety, efficacy, rational use, and storage conditions, 49.8% of respondents rated regulatory implementation practice as not satisfactory. In this study, most study participants raised concerns about the performance of quality control parameters. Among regulatory experts, weak performance was identified in the practical implementation of THM regulatory activities, with 70.2% of weak performance observed at the federal level and 41.7% at the regional level. Key barriers to effective regulation included a lack of research on herbal medicines (90.3%) and insufficient regulatory mechanisms (87.8%). Additional challenges for regulatory offices included traditional healers’ reluctance to engage with scientific communities (56.5%), inadequate inspections (55.3%), and limited data on the safety, quality, and efficacy of certain medicinal plants (54.4%).ConclusionOverall, the Ethiopian Food and Drug Authority (EFDA) is significantly strengthening the legislative and regulatory framework for traditional herbal medicines (THM), although full implementation is still forthcoming. This study highlights the need for comprehensive policy development, improved training initiatives, and reinforced regulatory systems to effectively monitor and regulate THM practices. For future roadmaps, collaboration among traditional healers, regulatory bodies, and scientific communities, along with supporting evidence-based research, could further enhance THM regulation in Ethiopia. These collaborative endeavors are critical for promoting the safety and quality of products derived from herbal medicines.